ANALISA PENGARUH RASIO KEUANGAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN PERIODE 2016 ”“ 2018 - Nurhasanah, Devi; Maryono, Maryono (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
The purpose of this study is to examine and analyze the effect of financial ratios analyzed in this study are asset adequacy ratios, non-performing loans, and profitability ratios using the Capital Adequacy Ratio (CAR), Non Performing Loan variables (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Return On Assets (ROA) in banking companies listed on the IDX for the 2016 - 2018 period. This study's population were all banking companies listed on the IDX for the 2016”“ 2018 period. The sampling method used was purposive sampling with a sample size of 40 banking companies. This analysis tool has used multiple linear regression. The results of these study are NIM has a positive effect on ROA, NPL has a negative effect on ROA, while CAR and LDR have no effect on ROA in banking companies listed on the IDX for the 2016 - 2018 period.